Cell Origin and iNOS Function Are Critical to Macrophage Activation Following Acute Lung Injury - Golden, Thea N.; Venosa, Alessandro; Gow, Andrew J (Frontiers in Pharmacology, 2022)
In the intratracheal bleomycin (ITB) model of acute lung injury (ALI), macrophages are recruited to the lung and participate in the inflammation and resolution that follows injury. Macrophage origin is influential in determining activation; however, the specific phenotype of recruited and resident macrophages is not known. Inducible nitric oxide synthase (iNOS) has been implicated in the pathogenesis of ALI, however the effects of its inhibition are mixed. Here we examined how macrophage origin determines the phenotypic response to ALI. Further, we hypothesize cell specific iNOS is key to determining activation and recruitment. Using a chimeric mouse approach, we have identified recruited and resident macrophage populations. We also used the chimeric mouse approach to create either pulmonary or bone marrow NOS2-/- mice and systemically inhibited iNOS via 1400W. We evaluated macrophage populations at the peak of inflammation (8 days) and the beginning of resolution (15 days) following ITB. These studies demonstrate tissue resident macrophages adopt a M2 phenotype specifically, but monocyte originated macrophages activate along a spectrum. Additionally, we demonstrated that monocyte originating macrophage derived iNOS is responsible for recruitment to the lung during the inflammatory phase. Further, we show that macrophage activation is dependent upon cellular origin. Finally, these studies suggest pulmonary derived iNOS is detrimental to the lung following ITB. In conclusion, macrophage origin is a key determinant in response to ALI and iNOS is central to recruitment and activation.